Marketing y la demanda de viviendas sostenibles en Perú: Marketing and the demand for sustainable housing in Peru - Álvarez Luján, Blanca Lina; Zulueta Cueva, Carlos Eduardo (Revista de Ciencias Sociales, 2021)
At present, climate change, the sustainability of cities and their relationship with sustainable housing are aspects of the real estate sector that are recognized and discussed by different international organizations, governments and other institutions. Therefore, the objective of this research was to define the marketing factors that influence the demand for sustainable housing in the population of Peru. Under a type of analytical-descriptive research, with a quantitative approach and non-experimental design - transversal; using the survey as a data collection technique and a structured questionnaire applied to a population of 410 non-homeowners households in the main cities of Peru, according to the Institute for the Mi Vivienda Fund in 2018; the data processing was carried out with the factorial analysis of principal components. As a result, it was obtained that the most important factors that influence the demand for sustainable homes are: Bioclimatic design of the home, marketing communication actions, economy of the demanding population, information related to the supply of sustainable homes, among others. It is concluded, that these factors can be used as lines of action to structure the sustainable marketing strategies of other similar projects.